Orthogonal Particle Swarm Optimization Algorithm and Its Application in Circuit Design - Xuesong Yan; Qinghua Wu; Hammin Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this paper, aim at the disadvantages of standard Particle Swarm Optimization (PSO) algorithm like being trapped easily into a local optimum, we improves the standard PSO and proposes a new algorithm to solve the overcomes of the standard PSO. The new algorithm keeps not only the fast convergence speed characteristic of PSO, but effectively improves the capability of global searching as well. Experiment results reveal that the proposed algorithm can find better solutions when compared to the standard particle swarm optimization algorithm. We use the proposed algorithm for digital circuit optimization design, and the final circuit is optimized in terms of complexity (with the minimum number of gates). DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2135